Объяснение:
1) 2Zn + O2 = 2ZnO
Zn(0) -2e = Zn(+2) 2 ок-ие
в-ль
O2(0) +4e = 2O(-2) 1 в-ие
ок-ль
2) ZnO + H2SO4 = ZnSO4 + H2O
ZnO + 2H(+)+ SO4(2-) = Zn(2+) + SO4(2-) + H2O
ZnO + 2H(+) = Zn(2+) + H2O
3) ZnSO4 + 2NaOH = Zn(OH)2 + Na2SO4
Zn(2+) + SO4(2-) + 2Na(+) + 2OH(-) = Zn(OH)2 + 2Na(+) + SO4(2-)
Zn(2+) + 2OH(-) = Zn(OH)2
4) ZnO + 2KOH = K2ZnO2 + H2O
ZnO + 2K(+) + 2OH(-) = 2K(+) + ZnO2(2-) + H2O
ZnO + 2OH(-) = ZnO2(2-) + H2O
5) Zn(OH)2 + 2KOH = K2ZnO2 + 2H2O
Zn(OH)2 + 2K(+) + 2OH(-) = 2K(+) + ZnO2(2-) + 2H2O
Zn(OH)2 + 2OH(-) = ZnO2(2-) + 2H2O
6) Zn(OH)2 + 2HCl = ZnCl2 + 2H2O
Zn(OH)2 + 2H(+) + 2Cl(-) = Zn(2+) + 2Cl(-)+ 2H2O
Zn(OH)2 + 2H(+) = Zn(2+) + 2H2O
ответ смотри во вложении